Detecting Herd Effect on Nordic stock markets : Evidence from Finland, Sweden, and Denmark - Lindblad, Meri (My University, 2025)
This master's thesis investigates herding behavior and how it transpires in the Nordic stock markets of Finland, Sweden, and Denmark, over the study period from 2013 to 2023. Herding behavior is characterized as an act when an investor discards their own information and knowledge and follows the market trend. By utilizing daily stock return data from the chosen markets, the thesis applies methodologies from previous herding investigations to detect market-wide herding under different market conditions and time frames. By utilizing CSAD methodology, the aim is to determine whether investors in the Finnish, Swedish and Danish stock markets exhibit herding behavior and additionally, if the herding behavior varies during different market conditions, such as up- and down- market times. The findings of this study conclude different herding results across the chosen stock markets. From the Swedish stock market, herding behavior can be detected and from the Finnish and Danish stock markets, no significant evidence of herding behavior is detected. The results suggest that Swedish investors are more affected by market trend, especially during extreme market movements. The no significant evidence of herding behavior from the Finnish and Danish markets, indicates a diverse response from investors under varying market conditions. The findings of this study provide insights to the prevailing knowledge on herding behavior in the Nordic stock markets. The Finnish and Danish stock markets are developed markets and have higher stock market efficiency, resulting in decreased occurrence of herding behavior. In Sweden, during extreme market movements, the Swedish investors have still had the tendency to exhibit herding behavior.

Tässä tutkielmassa tarkastellaan laumakäyttäytymistä ja sen ilmenemistä Pohjoismaisilla osakemarkkinoilla Suomessa, Ruotsissa ja Tanskassa tutkimusjaksolla 2013–2023. Laumakäyttäytyminen voidaan määritellä toimintana, jossa yksittäinen sijoittaja hylkää omat tietonsa ja asiantuntemuksensa ja seuraa muiden sijoittajien toimintaa markkinoilla eli markkinoiden yleistä suuntaa. Hyödyntämällä päivittäisiä osaketuottoja kyseisiltä markkinoilta, tutkielmassa pyritään havaitsemaan laumakäyttäytymistä erilaisissa markkinatilanteissa sekä eri ajanjaksoilla. CSAD-menetelmää hyödyntäen, tutkielman tavoitteena on selvittää, havaitaanko Suomen, Ruotsin ja Tanskan osakemarkkinoilta laumakäyttäytymistä ja lisäksi, vaihteleeko laumakäyttäytyminen eri markkinatilanteiden, kuten nousu- ja laskumarkkinoiden aikana. Tehdyn tutkielman tulokset paljastavat vaihtelevia laumakäyttäytymisen esiintymisiä tutkituilla osakemarkkinoilla. Ruotsin osakemarkkinoilla on havaittavissa laumakäyttäytymistä, kun taas Suomen ja Tanskan osakemarkkinoilla merkittävää näyttöä laumakäyttäytymisestä ei ole havaittavissa. Tutkimuksen tulokset viittaavat siihen, että Ruotsin osakemarkkinoiden sijoittajat reagoivat herkemmin markkinoiden suunnan muutoksiin. Se, että Suomen ja Tanskan markkinoilta ei ole havaittavissa laumakäyttäytymistä viittaa, että sijoittajat kyseisillä osakemarkkinoilla reagoivat eri tavoin markkinatilanteen muutoksiin. Tutkimuksen tulokset tarjoavat uutta tietoa Pohjoismaiden osakemarkkinoiden laumakäyttäytymisestä. Suomen ja Tanskan osakemarkkinat ovat kehittyneitä ja kyseisten markkinoiden markkinatehokkuus on korkea, mikä vähentää laumakäyttäytymisen ilmentymistä. Tutkimuksen tulokset viittaavat siihen, että Ruotsissa sijoittajilla on taipumusta laumakäyttäytymiseen muuttuvissa markkinatilanteissa.
Keywords: financial markets; Nordic countries; behaviour; herding; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance